Phonophoresis of Phyllanthus amarus nanoparticle gel improves functional capacity in individuals with knee osteoarthritis: A randomized controlled trial - Decha Pinkaew (2019)
© 2019 Elsevier Ltd Objective: This study examined the effects of treatment with Phyllanthus amarus nanoparticle gel applied by phonophoresis (PP)and ultrasound therapy (UT)in patients with symptomatic knee osteoarthritis (OA)using a randomized, double-blind, controlled trial. Methods: Patients with knee OA (n = 40; mean age ± SD, 64.30 ± 9.71 years), who had visual analogue scale (VAS)scores for knee pain intensity of 68.00 ± 9.58 (UT group)and 71.00 ± 8.74 (PP group, respectively)before treatment, were randomly allocated into two groups. Both groups were treated with an ultrasound program in continuous mode, 1.0 W/cm 2 , 10 min per session, for 10 sessions. Nanoparticles of P. amarus were used in the PP group, whereas a nondrug coupling gel was used in the UT group. The 6-min walk test (6-MWT)was performed to evaluate functional capacity. The VAS and the 6-MWT were evaluated before and after 10 treatment sessions in both groups using a double-blind procedure. Results: VAS and 6-MWT showed significant improvement after treatment in both groups (p < 0.05). The PP group showed more significant effects than the UT group, in terms of both reducing the VAS pain score (p < 0.05)and improving 6-MWT (p < 0.05). Conclusions: PP is suggested as an effective method for the treatment of symptomatic knee OA for reducing pain and improving functional capacity.